2009
DOI: 10.1177/0748730409335546
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Well-Being Is Modulated by Circadian Phase, Sleep Pressure, Age, and Gender

Abstract: Subjective well-being largely depends on mood, which shows circadian rhythmicity and can be linked to rhythms in many physiological circadian markers, such as melatonin and cortisol. In healthy young volunteers mood is influenced by an interaction of circadian phase and the duration of time awake. The authors analyzed this interaction under differential sleep pressure conditions to investigate age and gender effects on subjective well-being. Sixteen healthy young (8 women, 8 men; 20-35 years) and 16 older volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
3
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 42 publications
5
75
3
2
Order By: Relevance
“…These findings corroborate with those of the literature that show that sleep deprivation is associated with mood, tension and fatigue 14,15 , especially with the advance in age 14 . The study carried out by Faubel et al 25 found differences in mean SF-36 scores for all scale of the mental component in the adjusted analyses only in women, with a greater magnitude of association for role-emotional scale.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…These findings corroborate with those of the literature that show that sleep deprivation is associated with mood, tension and fatigue 14,15 , especially with the advance in age 14 . The study carried out by Faubel et al 25 found differences in mean SF-36 scores for all scale of the mental component in the adjusted analyses only in women, with a greater magnitude of association for role-emotional scale.…”
Section: Resultssupporting
confidence: 82%
“…Literature also suggests that good quality sleep provides for daily recovery from physical and mental stresses, improves mood, concentration and memory and reduces the risk of accidents 8,14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Stress can also disrupt the circadian cycle (Meerlo et al 2002), leading to depressive episodes in vulnerable individuals (Ehlers et al 1988). In addition, mood deteriorates with increases in the duration of prior wakefulness (Birchler-Pedross et al 2009;Boivin et al 1997). The nature of the circadian-homeostatic interaction is such that moderate changes in the timing of the sleep-wake cycle may have profound effects on subsequent mood.…”
Section: Sleep Disturbance Causes Waking Emotional Dysfunctionsmentioning
confidence: 99%
“…However in patients with Delayed Sleep Phase Syndrome, the onset of salivary melatonin, adjudged by a dim light onset test, was also delayed. Chrononutrition will almost certainly be important on changing temporal and constituent patterns of dietary intake and melatonin may be one determinant of subjective well-being [163].…”
Section: B) Melatoninmentioning
confidence: 99%